PTH-029 Helicobacter pylori-associated hypochlorhydria in children relates to the development of iron deficiency. (23rd September 2015) - Harris, P R; Villagran, A; Serrano, C; Duarte, I; Windle, H J; Crabtree, J E
Abstract : Introduction: Acute H pylori infection is associated with transient hypochlorhydria of variable duration. Hypochlorhydria in H pylori -associated atrophy has a role in iron deficiency (ID) through changes in the physiology of iron absorption. The role of hypochlorhydria in H pylori -associated ID in childhood has not been investigated. The aims were to evaluate the association between H pylori -associated hypochlorhydria and ID in children. Methods: A total of 123 children were prospectively enrolled in the study. Any child with peptic ulceration, or who received antacids, PPIs, H2 antagonists, and antibiotics in the previous 4 weeks was excluded. Blood was taken for complete blood count and iron profile. Gastric biopsies were taken for H. pylori determination by histology and rapid urease test. H pylori status was defined as +ve if either test was positive. Gastric juice was obtained at the beginning of the endoscopy avoiding water insufflation. Duodenal biopsies were taken for exclusion of coeliac disease (CD). Stool samples were collected for parasitology/microbiology. Of the 123 children, 2 with CD, 8 with non-specific duodenal inflammation (DI), 5 with lost blood analysis and 9 with parasitic infections (2 with DI) were excluded. Results: Of the remaining 101 children 31 were H pylori +ve and 10 were hypochlorhydric (pH>4). There were no differences in demographic characteristics with regard to infection status, or gastric pH. In H pylori +ve children with pH >4 (n=6) serum iron (median (IQR): 60.2 (45–66) μg/dl) and transferrin saturation levels percentage (16.6 (15–19)) were significantly lower (p<0.01) than H pylori positive children (n=25) with pH≤4 (iron 113.2 (91–132); transferrin saturation 32.6 (24–38)). No differences in ferritin or TIBC were observed. In H pylori negative children with pH>4 (n=4) both iron (119 (101–137)), and transferrin saturation (36.4 (31–41)), were not significantly different from children with pH≤4 (n=66) (iron 98.7 (80–122); transferrin saturation 32.2 (25–40)). Conclusion: Low serum iron and transferrin in childhood H pylori infection is associated with hypochlorhydria. In uninfected children, hypochlorhydria was not associated with altered serum iron parameters, indicating a combination of H pylori infection and/or inflammation and hypochlorhydria has a role in the aetiology of iron deficiency. Even though H pylori -associated hypochlorhydria may reflect a transient period during acute gastritis, it alters iron homeostasis with clinical impact in developing countries with a high H pylori prevalence. Funded by EU CONTENT Project (INCO-CT-2006-032136) and CONICYT/BM (RUE #29).